Haplanthus laxiflorus (Blume) Gnanasek., G.V.S.Murthy & Y.F.Deng (Acanthaceae): A New Generic Record for Nepal - Gupta, Satya; Poudel, Yogendra Bikram; Adhikari, Bhaskar; Lamichhane, Dipak; Parmar, Gaurav (Journal of Plant Resources, 2024)
Haplanthus laxiflorus (Blume) Gnanasek., G.V.S.Murthy & Y.F.Deng is reported here as a new generic record for the flora of Nepal. A detailed description, along with notes on habitat, distribution, photographs and a herbarium image have all been provided. This species can be easily distinguished by its distinctly pouched filaments inserted at the base of subactinomorphic corolla.